Analisis ramalan pelemahan hujan Semenanjung Malaysia menggunakan peta rekaan berkontur - Farah Aniza Nazri,; Nurul Syahira Mohamad Zamani,; Mandeep Jit Singh, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Rain weaken the signal wave through the absorption and dispersion of signal reception causing disturbance in satellite systems operating above 10 GHz frequencies. This phenomenon resulting rain attenuation occurs. Malaysia is a tropical country and experiencing a high rate of rainfal hence facing a huge disturbancel. The source of rainfall data used by this research are from the Department of Irrigation and Drainage Malaysia (DID) using a rain gauge Tipping Bucket method with rain gauge size diameter 0.25 mm per tip for measuring droplets of rainfall. One minute rain precipitate data were used to calculate the rainfall rate. precipitation rate calculation of rainfall. ITU-R model was selected according to the climate and levels of rainfall throughout the year as well as it is widely accepted on satellite communication systems research in the tropics. The rain attenuation in PenisularMalaysia were found in the range of 40-51 dB at 0.01% of time and was illustrated through contoured map. The result of this rain attenuation prediction can be used as reference to other researchers for continued research to improve and enhance the quality of transmission and reception of radio signals on satellite systems which operate over 10 GHz in tropical climate and high rainfall.